Privacy concerns and protection behavior during the Covid-19 pandemic - Ranjany Sundaram; Snehal Shetty (Problems and Perspectives in Management, 2022)
This paper aims to analyze the protection behavior of employees while working remotely during the Covid-19 pandemic using online video chat software. This pandemic changed the way organizations work, managers meet with employees, and employees communicate. An e-mail-based survey among computer users who use video chat software for remote working is employed in this study. Using 306 responses, structural equation modeling explores the relationship between privacy concerns, protection behavior, and antecedents. The technological changes induced due to Covid-19 influence privacy concerns and protection behavior. Privacy efficacy increases privacy concerns and protection behavior. Perceived vulnerability increases privacy concerns. Perceived effectiveness of organization software affects privacy concerns but does not affect protection behavior. There is a positive relationship between privacy concerns and protection behavior; however, this positive relation is negatively moderated by a propensity to trust. A finding of threat severity measure using Covid-19 factors concludes that both privacy concerns and protection behavior increased for online video chat software users. The theoretical model explicates 75% of variances in privacy concerns and 57% of variances in protection behavior. Every one-unit increase in Covid-19 induced changes regarding the work environment increases the privacy concern by 35%, and every one-unit increase in perceived effectiveness of organization software increases privacy concern by 22%. Every one-unit increase in the privacy concern increases the protection behavior by 48%, and every one-unit increase in privacy efficacy increases protection behavior by 59%. AcknowledgmentThe assistance provided by Arun Thottath in reaching out to survey participants was greatly appreciated.